Exploration of the Influence of Psychological Distress, Fear and Anxiety on Life Satisfaction: The Mediating Role of Sleep Disturbances - Akmal, Akmal; Azliyanti, Elfitra (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
This study aims to investigate the influence of psychological distress, fear and anxiety on life satisfaction, with sleep disturbances as a mediating variable. This study is motivated by the increasing prevalence of sleep disturbances due to emotional and psychological distress, which can significantly impact individual well-being. The research uses a quantitative approach with data collection through surveys of research subjects who meet certain criteria. Data analysis was conducted using the Structural Equation Modeling (SEM) method to test the direct and indirect relationships between variables. The research results indicate that psychological distress, fear and anxiety do not have a positive influence on life satisfaction (with path coefficients of 0.092; p=0.503 and -0.137; p=0.370, respectively). However, sleep disturbances have a significant influence on life satisfaction (path coefficient of 0.942; p=0.000). Additionally, sleep disturbances have been shown to mediate the relationship between psychological stress and life satisfaction (t=-3.715; p=0.000), as well as the relationship between anxiety and life satisfaction (t=-4.299; p=0.000). These findings emphasize the importance of sleep disturbances as a strong mediating factor in linking psychological stress and anxiety with life satisfaction. This research makes a significant contribution to understanding the psychological mechanisms that affect individual well-being and can serve as a basis for more effective mental health interventions.